Microwave-irradiated green synthesis of metallic silver and copper nanoparticles using fresh ginger (Zingiber officinale) rhizome extract and evaluation of their antibacterial potentials and cytotoxicity - Jahan, Israt; Erci, Fatih; Cakir-Koc, Rabia; Isildak, Ibrahim (TAYLOR & FRANCIS INC, 2021)
Herein the microwave-assisted green synthesis of both silver (Ag) and copper (Cu) nanoparticles (NPs) by microwave irradiation have been successfully carried out using fresh ginger rhizome extract. Different analytical methods were used for the characterization of the nanoparticles. The size distribution of AgNPs was found from the range of 2.68 nm to 42.69 nm, whereas for CuNPs the size range was run from 11.32 nm to 33.70 nm in diameter. From the antibacterial assay, we found that both silver and copper nanoparticles demonstrated significant potentials against tested bacterial strains. Besides,in vitrocytotoxic effects of NPs were also tested on the L929 mouse fibroblast cell line through XTT cell viability assay which confirmed the non-toxic nature of AgNPs and CuNPs at all tested concentrations. Thus, the obtained biological properties, suggested the use of rhizome extract ofZingiber officinalemediated non-toxic AgNPs and CuNPs in further biomedical and clinical applications.
Keywords: Microwave-irradiated synthesis; Zingiber officinale; silver nanoparticles; copper nanoparticles; biological activity; ASSISTED SYNTHESIS; BIOSYNTHESIS; Chemistry; Science & Technology - Other Topics